Association of eszopiclone, zaleplon, or zolpidem with complex sleep behaviors resulting in serious injuries, including death. Issue 6 (22nd April 2020) - Harbourt, Kelly; Nevo, Ofir N.; Zhang, Rongmei; Chan, Vicky; Croteau, David
Abstract: Purpose: To identify and analyze postmarketing cases of complex sleep behaviors (CSBs) resulting in serious injuries, including death, associated with eszopiclone, zaleplon, or zolpidem (Z‐drugs). Methods: Retrospective analysis of the U.S. Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) from 16 December 1992 through 27 February 2018 and medical literature using PubMed and EMBASE. We used random sampling and descriptive statistics. Results: We identified 66 cases that met inclusion and exclusion criteria, four of which were identified in the medical literature. Twenty cases reported death and 46 cases reported serious injuries in association with CSBs occurring after the use of a Z‐drug. Fatal cases described events, such as carbon monoxide poisoning, drowning, falls, hypothermia, motor vehicle collisions, and apparent completed suicide. Nonfatal cases resulting in serious injuries described events, such as accidental overdoses, falls, gunshot wounds, hypothermia, third‐degree burns, and self‐injuries or suicide attempts. Twenty‐two cases reported a previous episode of a CSB while taking a Z‐drug prior to the event reported in this case series. Conclusions: The FAERS and medical literature cases support the need for increased awareness of the consequences that may occur because of CSBs associated with the use of Z‐drugs. Therefore, to protect public health, regulatory actions were taken, including adding a Boxed Warning, a Contraindication in patients who have experienced a prior episode of a CSB with a Z‐drug, and updating the existing Warnings and Precautions. An FDA Drug Safety Communication was also disseminated to alert healthcare professionals and the public of this potential risk.